2002
DOI: 10.1007/s00125-002-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of neuropeptide Y in glucose sensing in the dorsal hypothalamus of streptozotocin diabetic rats – in vitro and in vivo studies of transmitter release

Abstract: Aims. Within the brain, subgroups of neurons respond differently to altered glucose concentrations. Identification of neuropeptide Y in hypothalamic neurons that sense glucose suggests a role for neuropeptide Y in glucose sensing. Using in vitro and in vivo techniques to monitor transmitter release, we investigated whether lowering glucose concentration affects the release of neuropeptide Y from the brain, and whether this process is altered in Type I (insulin-dependent) diabetes mellitus. Methods. Male Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A clinical study indicates that plasma immunoreactive (IR)-NPY and urinary IR-NPY concentrations are elevated in type 2 diabetic (T2D) patients with advanced nephropathy (10). Several studies, using T1D animal models such as the streptozotocin-diabetic rats, have demonstrated that NPY release is increased in the hypothalamus (11,12). The evidence implies that NPY may play a role in the pathogenesis of diabetes and DN.…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study indicates that plasma immunoreactive (IR)-NPY and urinary IR-NPY concentrations are elevated in type 2 diabetic (T2D) patients with advanced nephropathy (10). Several studies, using T1D animal models such as the streptozotocin-diabetic rats, have demonstrated that NPY release is increased in the hypothalamus (11,12). The evidence implies that NPY may play a role in the pathogenesis of diabetes and DN.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, it is still not known exactly how and at which site (decreasing) glucose concentrations are sensed. It is likely that both peripheral glucose sensors at the level of the pancreas, liver, portal vein and carotid bodies and central glucose sensing areas in the hypothalamus and brainstem contribute to the final response (46, 77–82). Information from peripheral as well as brainstem glucose sensors will be relayed directly to the CRH neurones via ascending noradrenergic and adrenergic fibres from the A1/C1 and A2/C2 cell groups in the brainstem (83).…”
Section: Discussionmentioning
confidence: 99%